Differential Action of Reelin on Oligomerization of ApoER2 and VLDL Receptor in HEK293 Cells Assessed by Time-Resolved Anisotropy and Fluorescence Lifetime Imaging Microscopy - Dlugosz, Paula; Tresky, Roland; Nimpf, Johannes (Frontiers in Molecular Neuroscience, 2019)
The canonical Reelin signaling cascade regulates correct neuronal layering during embryonic brain development. Details of this pathway are still not fully understood since the participating components are highly variable and create a complex mixture of interacting molecules. Reelin is proteolytically processed resulting in 5 different fragments some of which carrying the binding site for two different but highly homologous receptors, ApoER2 and VLDL receptor. The receptors are expressed in different variants in different areas of the developing brain. Binding of Reelin and its central fragment to the receptors results in phosphorylation of the intracellular adapter Dab1 in neurons. Here we studied the changes of the arrangement of the receptors upon Reelin binding and its central fragment at the molecular level in HEK293 cells by time-resolved anisotropy and fluorescence lifetime imaging microscopy. In the off-state of the pathway ApoER2 and VLDLR form homo or hetero-di/oligomers. Upon binding of full length Reelin ApoER2 and VLDLR homo-oligomers are rearranged to higher order receptor clusters which leads to Dab1 phosphorylation. When the central fragment of Reelin binds to the receptors the cluster size of homo-oligomers is not affected and Dab1 is not phosphorylated. Hetero-oligomerization, however, can be induced, but does not lead to Dab1 phosphorylation. Cells expressing only ApoER2 or VLDLR change their shape when stimulated with the central fragment. Cells expressing ApoER2 produce filopodia/lamellipodia and cell size increases, whereas VLDLR-expressing cells decrease in size. These findings demonstrate that the primary event in the canonical Reelin pathway is the rearrangement of preformed receptor homo-oligomers to higher order clusters. In addition the possibility of yet another signaling mechanism which is mediated by the central Reelin fragment independent of Dab1 phosphorylation became apparent.